2014
DOI: 10.1111/cea.12241
|View full text |Cite
|
Sign up to set email alerts
|

Immunological comparison of allergen immunotherapy tablet treatment and subcutaneous immunotherapy against grass allergy

Abstract: Both SCIT and SLIT tablet induce significant changes in specific antibodies (IgE and IgG4) and competition assays (IgE-blocking factor, FAP, and BAT). Overall, SCIT induced larger (two- to threefold) changes than SLIT tablet, with the exception of FAP, where SLIT tablet showed a gradual increase ending at the same level as SCIT. Maximal change was generally reached after 3 months' treatment.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
65
2
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 63 publications
(72 citation statements)
references
References 49 publications
4
65
2
1
Order By: Relevance
“…Facilitated allergen binding (FAB) inhibition after 1 month was less than 5% for SCIT and nonexistent for SLIT 30. Nevertheless, in our study, LPP immunotherapy led to FAB inhibition that after 4 weeks was 26.4% greater than that at baseline (370‐μg group).…”
Section: Discussioncontrasting
confidence: 60%
“…Facilitated allergen binding (FAB) inhibition after 1 month was less than 5% for SCIT and nonexistent for SLIT 30. Nevertheless, in our study, LPP immunotherapy led to FAB inhibition that after 4 weeks was 26.4% greater than that at baseline (370‐μg group).…”
Section: Discussioncontrasting
confidence: 60%
“…17,18,27 We found a significant inverse correlation when reaching maintenance between IgG 4 levels induced by AIT and the apparent reduction of the IgE signal, suggesting that an increase of greater than 0.56 ISU of IgG 4 (second and third tertiles) leads to a measurable decrease by competing with IgE for epitopes of the limited amount of allergen spotted on the chip. This is probably an underestimate of the suppressive effect of IgG 4 because the concentration of IgE to the major allergens Phl p 1 and Phl p 5 in simultaneous ImmunoCAP measurements increased significantly.…”
Section: Igg 4 Induced By Scit Suppresses Isac Ige Measurementsmentioning
confidence: 71%
“…25 ISAC measurement of IgE to treatment allergens is suppressed by AIT As in a previous study, 26 we found comparable pretreatment IgE concentrations with both ImmunoCAP and ISAC. SCIT upregulated allergen-specific IgE levels 17,18,27 when measured with the ImmunoCAP method where allergen is in excess. In contrast, signals in the ISAC measurement of allergen-specific IgE were significantly reduced by SCIT.…”
Section: Baseline Measurementsmentioning
confidence: 99%
“…Unlike the clinical responses, the 2 groups showed differences in their immunological responses, which are generally not confounded by placebo effect in AIT studies [33, 34]. The induced cross-reactive IgE is dependent on the BT sensitization.…”
Section: Discussionmentioning
confidence: 99%